Penerapan Prinsip-Prinsip Manajemen Pendidikan Islam: Studi Kasus Madrasah Ibtidaiyah Swasta Al-Ikhwan Bukittinggi, Sumatera Barat - Yusuf, M.; Iswantir, Iswantir (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
The management of madrasah educational institutions is currently changing significantly due to the paradigm it applies. This paradigm includes the application of the concept of buttom-up management. It focuses on improving quality through autonomy, accountability, accreditation and evaluation. The new paradigm encourages many to start a system based on values, transparency and public accountability. As an Islamic educational institution, Madrasahs retain their characteristics of adapting to change that distinguish them from other institutions. Its main source of teachings is Islam (Al-qur'an and Hadith) which inspires it. This research investigates the application of Islamic education management principles at MIS Al-Ikhwan Bukittinggi. This research uses a qualitative approach and descriptive-analytical method. This research aims to find out how well the madrasah applies the principles of Islamic education management, including the principles of shura, ikhlas, sidiq, amanah, and taqwa. Based on the information gathered through interviews and observations, the researcher found that the institution has implemented these principles. In addition, the vision and mission of the madrasah are in accordance with the principles of Islamic education management.